Efficacy of Breathing Techniques anEfficacy of Breathing Techniques and Positioning Strategies on Dyspnea and Nocturnal Symptoms in Patients with Chronic Obstructive Pulmonary Disease: A Systematic Reviewd Positioning Strategies on Dyspnea and Nocturnal Symptoms in Patients with Chronic Obstructive Pulmonary Disease: A Systematic Review - Ary Septri Mulainy; Agung Waluyo; Anggri Noorana Zahra (Indonesian Journal of Global Health Research, 2026)
Chronic Obstructive Pulmonary Disease (COPD) is a major global health burden and is projected by the World Health Organization (WHO) to become the third leading cause of mortality by 2030. This trend highlights the urgent need for multidisciplinary healthcare management to maintain patient stability and improve outcomes. Objective to evaluate the effectiveness of non-pharmacological breathing exercise techniques and patient positioning strategies in reducing dyspnea, enhancing lung function, improving nocturnal symptoms, and supporting overall quality of life in individuals with COPD. This systematic review followed PRISMA 2020 guidelines. Literature searches were conducted in PubMed, Scopus, ProQuest, EBSCO, SAGE Journals, ScienceDirect, and ClinicalKey using MeSH terms, keywords, and Boolean operators. The search strategy used combinations of the following main keywords: COPD, breathing exercise, breathing technique, positioning, pulmonary rehabilitation, dyspnea, nocturnal symptoms, sleep disturbances. Inclusion criteria were Randomized Controlled Trials (RCTs), adult participants (≥19 years) and publication years 2020–2025. A total of 2,695 articles were identified. After screening, removal of duplicates, and full-text assessment, 14 studies met the inclusion criteria. Analysis of the 14 included studies demonstrated that a variety of non-pharmacological breathing techniques particularly when combined with optimal patient positioning, pulmonary rehabilitation, supportive devices, complementary therapies, and virtual-reality–based interventions consistently improved lung function, functional capacity, dyspnea, and health-related quality of life in patients with COPD. None of the included studies reported adverse effects related to the interventions. Breathing exercise techniques and therapeutic positioning are effective non-pharmacological strategies for managing COPD symptoms.